2021
DOI: 10.3389/fgene.2021.676546
|View full text |Cite
|
Sign up to set email alerts
|

Shared Genetics Between Age at Menopause, Early Menopause, POI and Other Traits

Abstract: Reproductive ageing leading to menopause is characterized by depletion of follicles and its regulating mechanisms are only partly understood. Early age at menopause and premature ovarian insufficiency (POI) are associated with several other traits such as cardiovascular disease, dyslipidemia, osteoporosis and diabetes. In large cohorts of Northern European women hundreds of Single Nucleotide Polymorphisms (SNPs) have been identified to be associated with age at menopause. These SNPs are located in genes enrich… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 103 publications
(163 reference statements)
1
8
0
Order By: Relevance
“…In the Coronary Artery Risk Development in Young Adults Study, primiparas had increased waist-to-hip ratio compared with women who remained nulliparous during a 5-year follow-up, 26 although the mechanisms for this are unclear as others have reported that the effects of increased accretion of visceral fat on transient insulin resistance becomes resolved shortly postpartum 27 . Low parity has also been associated with an earlier age at natural menopause, which may lead to higher risk of cardiovascular disease in later life, 28 or impact different aspects of the aging process based on pleiotropic genetic influences 29 . In our study, we found that a one-child increase in parity was associated with an increase in BMI that persisted, although with smaller effect size, in the postmenopausal years, and this was not accompanied by an elevation in conventional cardiometabolic risk.…”
Section: Discussionmentioning
confidence: 99%
“…In the Coronary Artery Risk Development in Young Adults Study, primiparas had increased waist-to-hip ratio compared with women who remained nulliparous during a 5-year follow-up, 26 although the mechanisms for this are unclear as others have reported that the effects of increased accretion of visceral fat on transient insulin resistance becomes resolved shortly postpartum 27 . Low parity has also been associated with an earlier age at natural menopause, which may lead to higher risk of cardiovascular disease in later life, 28 or impact different aspects of the aging process based on pleiotropic genetic influences 29 . In our study, we found that a one-child increase in parity was associated with an increase in BMI that persisted, although with smaller effect size, in the postmenopausal years, and this was not accompanied by an elevation in conventional cardiometabolic risk.…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiological studies have shown that early menopause and loss of ovarian function are strongly correlated with shorter life span and elevated risk of metabolic, cardiovascular, and osteoporosis disease, among others [3][4][5]. GWAS and WES studies have identified 290 loci that associate with age at natural menopause [9], some of which overlap with the >100 genes currently linked to POI [35,36].…”
Section: Discussionmentioning
confidence: 99%
“…Primary ovarian insufficiency (POI) is a condition that affects 1-5% of women and is defined by the cessation of menstruation before the age of 40 [1,2]. Early menopause is linked to shorter life span, increased risk of diabetes mellitus, heart disease, cardiovascular disease, and osteoporosis [3][4][5]. Similarly, lower sperm counts are an independent predictor of comorbidity and mortality [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…This meta-analysis indicated that levels of serum lipid profile were remarkably altered in patients with primary ovarian insufficiency: levels of serum TC, TG and LDL in women with POI were significantly higher than that in healthy controls, however, no significant difference was observed regarding the level of serum HDL between women with POI and healthy controls. Women with POI present several risk factors for the occurrence and development of CVD: autonomic and endothelial dysfunction, insulin dysfunction, abnormal lipid profile (33), genetic variants associated with early menopause (34,35). Diminished ovarian response to FSH is thought to cause the occurrence and development of atherosclerosis based on non-human primate models (36) and studies of hypothalamic angiography (37).…”
Section: Discussionmentioning
confidence: 99%